Producing hybrid forests in the Congo Basin: A political ecology of the landscape approach to conservation. (November 2016) - Clay, Nathan
Highlights: Logging and conservation in the Congo Basin are coordinated through a "landscape approach." In practice, the landscape approach is translated through hybrid governance negotiations. The landscape approach permits collusion among powerful actors to define ecosystem function. Place-based knowledge of local actors is overlooked, leading to further livelihood marginalization. A landscape approach must adaptively manage new dynamics of society-environment interaction. Abstract: Environmental conservation is increasingly operated through partnerships among state, private, and civil society actors, yet little is known empirically about how such collectives function and with what livelihood and governance outcomes. The landscape approach to conservation (known also as the ecosystem approach) is one such hybrid governance platform. Implemented worldwide over the past decade by international NGOs, the landscape approach employs the 'ecosystem principles' of the Convention on Biological Diversity (CBD). In spite of its prominence as a conservation and development strategy, little political ecology scholarship has considered the landscape approach. This article offers a case study of a conservation landscape in the Congo Basin, the Tri-National de la Sangha (TNS), which connects tropical forests in Cameroon, Republic of Congo, and Central African Republic. Led by NGOs, the TNS has since 2001 relied on partnerships among logging companies, safari hunters, the state, and local communities. Although the landscape approach purports to facilitate re-negotiations of user rights, resource access patterns in the TNS appear to have molded to pre-existing power relations. Rather than incorporating local concerns and capabilities into management, local knowledge is discredited and livelihoods are marginalized. As a result, management occurs through spatially-demarcated zones, contrasting the fluidity of interactions among diverse groups: both human (loggers, hunter-gatherers, safari guides, NGOs) and non-human (trees, elephants). These findings are situated within a burgeoning literature on neoliberal environmental governance, and suggest that ensuring ecologically and socially positive outcomes will require careful and iterative attention to linkages between ecological processes and evolving power dynamics.